Missa Est! : a missional liturgical ecclesiology - Schlesinger, Eugene R. (Emerging scholars., 2017)
Missa Est! is a constructive work in ecclesiology, and particularly the relationship between liturgy and mission in the church's life. It advances a notion of the church in which liturgy and mission are both given their due without opposing them to each other, subordinating one to the other, or collapsing them into each other. Mission and liturgy are intrinsically related to each other, for the church's liturgical rites disclose and enact the church's identity as a missionary community.